1997
DOI: 10.1046/j.1365-2958.1997.5081871.x
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA release from ribosomes during 5′‐translational blockage by consecutive low‐usage arginine but not leucine codons in Escherichia coli

Abstract: SummaryIn '5Ј-translational blockage', significantly reduced yields of proteins are synthesized in Escherichia coli when consecutive low-usage codons are inserted near translation starts of messages (with reduced or no effect when these same codons are inserted downstream). We tested the hypothesis that ribosomes encountering these low-usage codons near the translation start prematurely release the mRNA. RNA from polysome gradients was fractionated into pools of polysomes and monosomes and a ribosome-free pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Because the His-tag is at the end of the protein, only full-length proteins will be tagged and proteins truncated by premature termination of translation will not be purified by the Ni-IMAC column. Such premature termination occurs with some mammalian proteins expressed in prokaryotes, resulting in multiple bands of overexpressd proteins on gels, and can in many cases be attributed to frame shifts or release of message from the ribosome at rare codons [3234]. The use of strains that produce elevated amounts of rare tRNAs largely obviates this problem, but does not eliminate it completely.…”
Section: Discussionmentioning
confidence: 99%
“…Because the His-tag is at the end of the protein, only full-length proteins will be tagged and proteins truncated by premature termination of translation will not be purified by the Ni-IMAC column. Such premature termination occurs with some mammalian proteins expressed in prokaryotes, resulting in multiple bands of overexpressd proteins on gels, and can in many cases be attributed to frame shifts or release of message from the ribosome at rare codons [3234]. The use of strains that produce elevated amounts of rare tRNAs largely obviates this problem, but does not eliminate it completely.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that the generation of synonymous codons may influence the mRNA structure [42], the translation efficiency [43], and the protein folding and tertiary structure [44]. For example, it was shown that some highly expressed genes of E. coli [45], S. cerevisiae [46] and B. subtilis [47] have a strong preference for codons recognized by the most abundant tRNA species, which promotes translational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 20 years, experimental studies reported various phenotypic effects associated with modification of sequences codon usage: alteration of mRNA structure [32],[33], modification of translation efficiency [34],[35], and protein aggregation due to alteration of folding route and final tertiary structure [36][38]. Although a recent report has linked a phenotypic effect to the presence of two weakly used codons combined with a non-synonymous SNP [39], to the best of our knowledge no significant impact of a single rare codon has ever been described, most likely because it should involve a decrease in protein synthesis too weak to be measured accurately.…”
Section: Discussionmentioning
confidence: 99%